(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores modern concepts of green financing, specifically the achievement of sustainable economic growth through green bonds and ecological investments. The study analyzes the ecologically oriented transformation of financial markets, the incentive mechanisms created for investors, and the practical implementation of green finance in Uzbekistan. In addition, based on international experience, the article identifies promising financial mechanisms and provides relevant recommendations.